KARAKTERISTIK PESERTA DIDIK DALAM HADIST NABI MUHAMMAD SAW - Muhammad Husnurridlo Az Zaini; Nur Saidah (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2021)
Learners are the object of education. So that students are considered as raw materials in the educational transformation process. As a result, he must be forged to develop his abilities and skills in various aspects, both cognitive, affective, and psychomotor. For the above development optimally, it must be supported by a synergistic education program. In relation to Islamic education, these factors must synergize and be integrated based on the texts, namely the Qur'an and Hadith. In terms of students, there are three things that are urgent to discuss, namely 1) the potential of students, 2) the needs of students, 3) the nature of students. In this article using the library research method.